Design and Development of a Portable Beverage Cooling System Using a Heatsink and Wind Tunnel Fan Based on the Peltier Effect - Muhammad Adinda Hadinur; Komarudin Komarudin (Greenation International Journal of Engineering Science, 2025)
Development system cooler portable become important along increasing need cooling practical without use refrigerant and compressor . System cooler based The Peltier effect offers solution friendly environment and size compact , but performance is greatly influenced by ability disposal hot on the side hot module . Research This aim design and build system cooler drink portable based Peltier module with optimization mechanics using a heatsink and wind tunnel fan. Research methods covering design mechanics , manufacturing prototype , as well as testing performance thermal through measurement temperature side hot , side cold , temperature drinks and consumption Power electricity . The test results show that the system is able to achieve a minimum cold side temperature of 12 °C, a cooling chamber temperature of 16 °C, and reduce the beverage temperature by up to 5 °C within a 30-minute test duration. The use of a heatsink combined with a wind tunnel fan has been shown to increase the effectiveness of heat dissipation, thereby maintaining the stability of the Peltier module's performance. This system has the potential to be developed as an alternative small-scale portable cooler with low power consumption.